0
$\begingroup$

I was solving the following limit: $$\lim_{x\to -\infty}{\sqrt{x^2+x+1} - \sqrt{1-x+x^2}}$$

The limit itself is not too difficult ( expand to a fraction and just solve it, remembering the $-$ ) but the solution given in the manual is what troubles me. The solution goes as follows: $${\sqrt{x^2+x+1} - \sqrt{1-x+x^2}} = -x\bigg({\sqrt{1+\frac{1}{x}+\frac{1}{x^2}} - \sqrt{1 - \frac{1}{x} + \frac{1}{x^2}}}\bigg)$$ $$-x\bigg({\sqrt{1+\frac{1}{x}+\frac{1}{x^2}} - \sqrt{1 - \frac{1}{x} + \frac{1}{x^2}}}\bigg) = -x\bigg[ \bigg( 1 + \frac{1}{2}\big(\frac{1}{x}+\frac{1}{x^2}\big) + o\big( \frac{1}{2}\big(\frac{1}{x}+\frac{1}{x^2}\big) \big) - \bigg( 1 + \frac{1}{2}\big(-\frac{1}{x}+\frac{1}{x^2}\big) + o\big( \frac{1}{2}\big(-\frac{1}{x}+\frac{1}{x^2}\big) \big) \bigg) \bigg]$$

Which of course is $-1$ as $x$ approaches $-\infty$. While i understand the $o$ notation , I still have a questions here:

  • How is $${\sqrt{1+\frac{1}{x}+\frac{1}{x^2}}} = 1 + \frac{1}{2}\big(\frac{1}{x}+\frac{1}{x^2}\big) + o\big( \frac{1}{2}\big(\frac{1}{x}+\frac{1}{x^2}\big) \big)$$ when $x\to -\infty$.
$\endgroup$
1
$\begingroup$

HINT:

Let $-1/x=h$ $$x^2+x+1=\dfrac{1+h+h^2}{h^2},\sqrt{1+x+x^2}=\dfrac{\sqrt{1+h+h^2}}{\sqrt{h^2}}$$

Now as $h>0,\sqrt{h^2}=|h|=+h$

$$\lim_{x\to -\infty}{\sqrt{x^2+x+1} - \sqrt{1-x+x^2}} =\lim_{h\to0^+}\dfrac{\sqrt{1+h(h-1)}-\sqrt{1+h(h+1)}}h$$

Now using Taylor's Expansion, $$\sqrt{1+h(h-1)}=\{1+h(h-1)\}^{1/2}=1+\dfrac{h(h-1)}2+o(h^2)$$

$$\sqrt{1+h(h+1)}=\{1+h(h+1)\}^{1/2}=1+\dfrac{h(h+1)}2+o(h^2)$$

If Taylor's Expansion is not mandatory, $$\sqrt{1+h(h-1)}-\sqrt{1+h(h+1)}=\dfrac{1+h(h-1)-\{1+h(h+1)\}}{\sqrt{1+h(h-1)}+\sqrt{1+h(h+1)}}=\dfrac{-2h}{\sqrt{1+h(h-1)}+\sqrt{1+h(h+1)}}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.